Pengembangan Pembelajaran Motorik Sd Se-Kecematan Topos Berbasis Permainan Tradisional Rakyat Kabupaten Lebong Provinsi Bengkulu - Salman, Erick; Darsi, Helvi (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This research aims to understand the development of elementary school motoric learning in the Topos sub-district based on traditional folk games in Lebong district, Bengkulu Province. The method used in this research is the research and development (R&D) method using the Dick and Carey model approach. The data collection techniques used in this research were interviews, observations, and questionnaires and conducting observations and interviews with PJOK teachers and homeroom teachers at SD Negeri 28 Lebong and SD Negeri 39 Lebong regarding PJOK learning related to games. The results of this research show that: the quality of the book seen from the validity aspect is included in the valid category, the results of the language expert's assessment with a score of 0.88, the results of the material expert's assessment with a score of 0.8, while the results of the media expert's assessment with a score of 0.807; The quality of the book seen from the practical aspect is categorized as very practical, the results of the teacher response practicality assessment were with a score of 4, the results of the one to one practicality test were with a score of 3.9, while the results of the small group test were with a score of 4.0. From the research we have conducted, we will produce scientific works such as teaching materials in the form of books and national journals accredited by Sinta 3. The conclusion is that traditional game books were developed using the 4-D model, including 4 stages, namely; Define (planning); Design (design); Develop (development), and Disseminate (deployment). Keywords: Development, Motor, Traditional Games.